Food processing, transformation, and job creation: The case of Ethiopia’s enjera markets - Minten, Bart; Assefa, Thomas; Abebe, Girum; Engida, Ermias; Tamru, Seneshaw (International Food Policy Research Institute, 2016)
Given the importance of agriculture in developing economies, food processing industries often dominate the industrial sector when considering employment and value addition in these settings. For example, it is estimated that the food processing industry in Ethiopia employs 1 million people, around 2 percent of the economically active population. However, the way this food processing industry is changing and how it functions is little understood. Based on a unique survey, we study the case of markets in urban Ethiopia for commercial ready-to-eat enjera, the traditional staple pancake of the country. We find that commercial enjera markets are quickly growing, employing more than 100,000 people in urban Ethiopia. Moreover, enjera is now being prepared by mixing flour from locally produced teff with that of imported rice, thus absorbing an important part of the rapidly growing rice imports (almost 200 million USD in 2015) in the country, and leading to higher profits for those enterprises engaged in this type of mixing. Increasing numbers of enjera-making enterprises (EMEs) – which mostly employ women – are emerging. Further, we note upscaling by those enjera-making enterprises that supply the growing urban food service sector. Larger enjera-making companies have better quality, different procurement mechanisms and technologies, and higher value-added. These findings are important for the policy debates in Ethiopia on food systems transformation, employment and job creation, and international trade.